2017
DOI: 10.1016/j.ajo.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Refractive Error in Adult Chinese Americans: The Chinese American Eye Study

Abstract: Purpose To estimate the prevalence of refractive errors in adult Chinese Americans, and evaluate factors associated with myopia and high myopia. Design A population-based, cross-sectional study. Methods Chinese Americans 50 years and older residing in Monterey Park, California, were recruited. Noncycloplegic automated refraction with supplemental subjective refraction was performed. Myopia, high myopia, hyperopia, and high hyperopia were defined as a spherical equivalent of < −0.5 diopter (D), < −5.0D, > +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
3
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 39 publications
9
57
3
6
Order By: Relevance
“…From a viewpoint of ethnicity difference, Chinese have a substantially higher prevalence of myopia compared with other racial groups, and a similar pattern of even greater magnitude was seen in HM prevalence. The prevalence of myopia and HM in Chinese ethnicity in western countries is similar to other studies of Chinese in urban Asian countries [80].…”
Section: Generational Gapsupporting
confidence: 87%
See 1 more Smart Citation
“…From a viewpoint of ethnicity difference, Chinese have a substantially higher prevalence of myopia compared with other racial groups, and a similar pattern of even greater magnitude was seen in HM prevalence. The prevalence of myopia and HM in Chinese ethnicity in western countries is similar to other studies of Chinese in urban Asian countries [80].…”
Section: Generational Gapsupporting
confidence: 87%
“…In the USA, the latest report in the Chinese American study showed the relatively high prevalence of myopia and HM, 35.1% and 7.4%, respectively, in 4144 Chinese adults aged 50 years or older [80]. This result is similar to or slightly higher than same Chinese populations from other studies in urban Asian countries (38.7% in the Tanjong Pagar Study, Singapore and 32.3% in the Liwan Eye Study).…”
Section: Non-asian Countriessupporting
confidence: 68%
“…After excluding participants diagnosed with cataracts, the prevalence of hyperopia increased with age in both ethnic groups. The age-related change in prevalence was also concluded in previous studies [26,30,31].…”
Section: Discussionsupporting
confidence: 77%
“…To eliminate the effects of noncycloplegic refraction, we compared the prevalence of myopia in the Han ethnicity in the 50-59 age group (30.8%) with other studies. We found that the prevalence of myopia in our study was higher than that in He J's study in Shanghai (23.2%) [26] the Handan eye study (18.2%) [25] and the Yunnan minority eye studies (5.0%) [21] in the same age group but lower than that in the Chinese American study (36.1%) [30] the Tajimi study (49.6%) [32], the Hong Kong vision study (40%) [33], the Singapore epidemiology of eye disease study (38.9%) [11], Korea national health and nutrition examination survey (55.2% in 45-49 age group) [34], and close to values from the Liwan study (31.7%) [24,31] and The Kumejima study (29.4%) [35] Table. 5 . The prevalence of high myopia in the Han ethnicity in the 50-59 age group was 5.0%, which was higher than the prevalence in the Handan Eye study (1.8%) [25], the Andhra Pradesh eye disease study (4.8%)[36] and the Kumejima study (0.8%) [35], but lower than that in the Liwan Study (5.3%) [24], The Shanghai Eye study (5.23%) [26] the Chinese American study (7.4%) [30], the Singapore epidemiology of eye disease study (5.1%) [11] and the Tajimi study (8.7%) [32].…”
Section: Discussioncontrasting
confidence: 75%
“…The prevalence of regular astigmatism (0.5 DC < Cylinder < 2.00 DC) was published as 45.6% out of 4144 participants from the Chinese American Eye Study [1] and Young et al reported a prevalence of 47.4% in relation to a contact lens wearing population [2]. Ohlendorf et al [3] reported a prevalence of 55% for astigmatism greater 0.5 DC in German study cohort of 655 adults.…”
Section: Introductionmentioning
confidence: 99%